Identities in transition : challenges for transitional justice in divided societies / edited by Paige Arthur. - Arthur, Paige (Cambridge University Press, 2011)
In many societies, histories of exclusion, racism and nationalist violence often create divisions so deep that finding a way to deal with the atrocities of the past seems nearly impossible. These societies face difficult practical questions about how to devise new state and civil society institutions that will respond to massive or systematic violations of human rights, recognize victims and prevent the recurrence of abuse. Identities in Transition: Challenges for Transitional Justice in Divided Societies brings together a rich group of international researchers and practitioners who, for the first time, examine transitional justice through an 'identity' lens. They tackle ways that transitional justice can act as a means of political learning across communities; foster citizenship, trust and recognition; and break down harmful myths and stereotypes, as steps toward meeting the difficult challenges for transitional justice in divided societies.